A 4D-Printed Structure With Reversible Deformation for the Soft Crawling Robot - Duan, Guifang; Liu, Han; Liu, Zhenyu; Tan, Jianrong (Frontiers in Materials, 2022)
Reversible deformations of the 4D-printed structures are attractive and promising for various application fields. In this study, the principle of reversible deformations for the bilayer structure consisting of SMP and elastic material is illustrated. By exploring the influence of printing parameters on deformation and resistance, a low-cost reversible bilayer structure with rational resistance distribution is designed to realize reversible deformation. Subsequently, the bilayer structure is employed to design a soft crawling robot with asymmetrical variable friction coefficient feet. By revealing the principle of locomotion by force analysis and deformation process analysis, a wave-like strategy is proposed to actuate the robot. Experiments verify the effectiveness of the designed structures.